Effect of immersion of larvae at multiple doses sumbawa honey on sex ratio and growth of Nile tilapia, Oreochromis niloticus (Linnaeus, 1758) - Neri Kautsari; Siti Rahma; Dedy Syafikri (Masyarakat Iktiologi Indonesia (Indonesian Ichthyological Society), 2015)
One of the efforts of farmers to improve their production is through the cultivation of single sex populations (monosex) male. Honey is a natural ingredient that contains crysin and aromatase inhibitors that play a role in the process of mas-culinization of fish. This study aimed to determine the effect of immersion larvae of tilapia Oreochromis niloticus (L) on media containing multiple doses of sumbawa honey against sex ratio, growth and growth rate. The experimental method with a completely randomized design was used. The amount of treatment used in this study was four treatments (0 ml L-1, L-1 10 ml L-1, 20 ml L-1, and 30 ml L-1) with three replications. Each treatment consisting of 30 fish. Immersions of larvae for 12 hours. To determine the effect of a dose of honey sumbawa to all parameters, ANOVA (analysis of variance) at the level of 95% was performed. The results showed that differences in honey doses given in the immersion process did not have a significant effect on the sex ratio and growth of tilapia. Abstrak Salah satu usaha pembudidaya dalam meningkatkan produksi adalah dengan cara memelihara populasi tunggal kelamin (monoseks) jantan. Madu merupakan salah satu bahan alami yang mengandung crysin dan penghambat aromatase ber-peran dalam proses pemaskulinan ikan. Penelitian ini bertujuan untuk mengkaji pengaruh perendaman larva ikan nila Oreochromis niloticus (L) dalam media pemeliharaan yang mengandung beberapa dosis madu sumbawa terhadap nisbah kelamin, pertumbuhan, dan laju pertumbuhan. Metode yang digunakan adalah eksperimen Rancangan Acak Leng-kap satu faktor, dengan perlakuan dosis madu sumbawa (0 ml L-1, 10 ml L-1, 20 ml L-1, dan 30 ml L